The Level of Expression of Anxiety and Depression in Clinical Health Care Workers during the COVID-19 Outbreak in 2 Hospitals in Hanoi, Vietnam - La Ngoc Quang; Nguyen Trung Kien; Pham Ngoc Anh; Dang Thi Van Anh; Tran Do Bao Nghi; Pham Phuong Lan; Nguyen The Anh; Nguyen Van Son; Nguyen Thi Thuy Lieu (SAGE Publishing, 2021)
The disease caused by the SARS-Cov 2 virus has spread to most areas of the world with high rates of infection and deaths. Facing the complicated developments of the epidemic, clinical medical staff (CMS) are at risk of suffering psychological pressure. This study aimed to investigate the situation of anxiety, depression, and related factors affecting CMS during the COVID-19 pandemic at Dong Da General Hospital and Dong Anh General Hospital in Hanoi. A cross-sectional study was conducted from April to July 2020 using self-administered questionnaires amongst 341 CMS. The participants' anxiety levels were assessed using the standardized General Anxiety Disorder-7 (GAD-7) toolkit and levels of depression expression were assessed based on the standardized Patient Health Questionnaire-9 (PHQ-9) toolkit. Of the CMS who completed the questionnaire, 33.1% had an anxiety disorder and 23.2% exhibited mild to very severe depression. The factors associated with anxiety and depression were department of work, shortage of human resources, and discrimination from the community that directly affects the family of the CMS. The study results highlight the need for a training session to equip CMS with the skills required to cope with psychological stress in all circumstances in general and during the pandemic in particular. This training is especially important for those working in at-risk departments which are susceptible to infection.